2022
DOI: 10.3390/land11081201
|View full text |Cite
|
Sign up to set email alerts
|

Native or Exotic: A Bibliographical Review of the Debate on Ecological Science Methodologies: Valuable Lessons for Urban Green Space Design

Abstract: Knowledge from ecological sciences is an important reference for landscape design as Urban Green Spaces (UGS) play a critical role in the ecological protection of cities. There is an ongoing debate among ecologists on the value of exotic vegetation to ecosystem resilience and integrity, with authors arguing that in order for ecosystems to survive in future climates, exotic species with similar conditions in their current range must be considered. Others deem biodiversity vital for ecosystem functions and servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 127 publications
0
15
1
Order By: Relevance
“…Across all cluster groups, people valued the species attribute "provide food and habitats for wildlife" much more important than "native plant species," with a mean score difference ranging from 0.7 to 1. A recent review study by de Carvalho et al (2022) indicated general views that native plant species favor and support native fauna, and exotic plant species negatively affect native fauna and also support exotic fauna. Over the decades, various studies showed that exotic plants could decrease the food availability for insects that feed on plant tissues (Sjöman et al 2016), and native plants were more likely to provide resources for urban animals and increase biodiversity in UGS (Mohamad et al 2013, Berthon et al 2021.…”
Section: Commonality Of Respondents' Evaluationsmentioning
confidence: 99%
“…Across all cluster groups, people valued the species attribute "provide food and habitats for wildlife" much more important than "native plant species," with a mean score difference ranging from 0.7 to 1. A recent review study by de Carvalho et al (2022) indicated general views that native plant species favor and support native fauna, and exotic plant species negatively affect native fauna and also support exotic fauna. Over the decades, various studies showed that exotic plants could decrease the food availability for insects that feed on plant tissues (Sjöman et al 2016), and native plants were more likely to provide resources for urban animals and increase biodiversity in UGS (Mohamad et al 2013, Berthon et al 2021.…”
Section: Commonality Of Respondents' Evaluationsmentioning
confidence: 99%
“…There is an ongoing debate among factions of landscape architects and, to a lesser extent, ecologists, on the role of exotic vegetation within managed landscapes [34]. One side argues that, in the face of climate change, a plant's adaptability and the ecosystem services they provide are more important than their geographic place of origin (for example, [35][36][37] The other side argues that a massive loss of biodiversity is underway due to the effects of climate change, biological invasion, and human disturbance and that the introduction of exotic vegetation (including lawns) further contributes to the losses [38][39][40][41].…”
Section: Perception-effects Of Native Plants On Urban Dwellersmentioning
confidence: 99%
“…Although not all introduced plants become invasive [ 17 , 18 ], the ability to become invasive should not be underestimated, both for casual and naturalized alien taxa [ 19 ]. Alien taxa are often introduced into urban green spaces, having more advantages than disadvantages compared to native species [ 20 ].…”
Section: Introductionmentioning
confidence: 99%